Genome‐wide identification of pathogenicity, conidiation and colony sectorization genes in Metarhizium robertsii. (29th May 2017) - Zeng, Guohong; Chen, Xiaoxuan; Zhang, Xing; Zhang, Qiangqiang; Xu, Chuan; Mi, Wubin; Guo, Na; Zhao, Hong; You, Yue; Dryburgh, Farah‐Jade; Bidochka, Michael J.; St. Leger, Raymond J.; et al.
Summary: Metarhizium robertsii occupies a wide array of ecological niches and has diverse lifestyle options (saprophyte, insect pathogen and plant symbiont), that renders it an unusually effective model for studying genetic mechanisms for fungal adaptation. Here over 20, 000 M. robertsii T‐DNA mutants were screened in order to elucidate genetic mechanism by which M. robertsii replicates and persists in diverse niches. About 287 conidiation, colony sectorization or pathogenicity loci, many of which have not been reported in other fungi were identified. By analysing a series of conidial pigmentation mutants, a new fungal pigmentation gene cluster, which contains Mr‐Pks1, Mr‐EthD and Mlac1 was identified. A conserved conidiation regulatory pathway containing Mr‐BrlA, Mr‐AbaA and Mr‐WetA regulates expression of these pigmentation genes. During conidiation Mr‐BlrA up‐regulates Mr‐AbaA, which in turn controls Mr‐WetA. It was found that Hog1‐MAPK regulates fungal conidiation by controlling the conidiation regulatory pathway, and that all three pigmentation genes exercise feedback regulation of conidiation. This work provided the foundation for deeper understanding of the genetic processes behind M. robertsii adaptive phenotypes, and advances our insights into conidiation and pigmentation in this fungus.